PENERAPAN METODE PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PENGUKURAN DEBIT PADA SISWA KELAS VI SEMESTER I SDN 2 KETEGUHAN BANDAR LAMPUNG - Kusrina, Kusrina (STKIP PGRI Bandar Lampung, 2021)
This research is based on problems raised from the low learning outcomes of mathematics. Of the 30 students, only 11 students or 36.7% scored above the KKM. While the objectives of this study are: (1) To find out the increase in mathematics learning activities measuring discharge material through the STAD model in class VI SD Negeri 2 Keteguhan, Teluk Betung Barat District, Bandar Lampung City for the 2019/2020 Academic Year. (2) To see an increase in student learning achievement through the STAD model in KPK and FPB learning in class VI-B SD Negeri 2 Keteguhan, Teluk Betung Barat District, Bandar Lampung City for the 2019/2020 Academic Year. This research uses action research as many as three rounds. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is the sixth grade students of SDN 02 Keteguhan, Teluk Betung Barat Subdistrict, Bandar Lampung City, Academic Year 2019/2020. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I (53.3%), cycle II (66.7%), cycle III (86.7%). Thus, STAD Learning Method has a positive influence on mathematics learning outcomes for grade VI students of SDN 2 Keteguhan, Teluk Betung Barat District, Bandar Lampung City for the 2019/2020 Academic Year, and this learning model can be used as an alternative for learning mathematics.